2017
DOI: 10.1002/mop.30629
|View full text |Cite
|
Sign up to set email alerts
|

A novel UHF Minkowski fractal antenna for partial discharge detection

Abstract: A compact and wideband ultra‐high‐frequency antenna is developed in this work. Based on the Minkowski fractal geometry of the lateral boundaries of monopole and the upper boundary of ground plane, miniaturization is realized. Meanwhile, by optimizing the dimension of the semi‐elliptical part of monopole and the triangular notch of ground plane, the impedance bandwidth is enhanced. To confirm the performance of antenna, a series of experiments are conducted. The size and ratio bandwidth of antenna are compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 17 publications
(18 reference statements)
0
9
0
Order By: Relevance
“…The microstrip antenna is also proposed in the literature for PD detection in the UHF domain [ 43 , 52 , 53 , 54 , 55 ]. The basic structure of the microstrip antenna is shown in Figure 4 b.…”
Section: Uhf Sensors In Partial Discharge Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The microstrip antenna is also proposed in the literature for PD detection in the UHF domain [ 43 , 52 , 53 , 54 , 55 ]. The basic structure of the microstrip antenna is shown in Figure 4 b.…”
Section: Uhf Sensors In Partial Discharge Detectionmentioning
confidence: 99%
“…A fractal antenna is one type of microstrip antenna with distinctive performance in UHF signal coupling and can offer miniaturization and wide bandwidth. Wang et al [ 52 ] designed a Minkowski fractal antenna and found that the order of the fractal curve can significantly affect the performance of the antenna. The Hilbert fractal antenna was proposed for PD detection in [ 56 , 57 , 58 ], and it was found that the fourth-order Hilbert fractal structure shown in Figure 5 d is appropriate for multiple-resonance filter design.…”
Section: Uhf Sensors In Partial Discharge Detectionmentioning
confidence: 99%
“…Monopole antenna is where different types and lengths of the monopole antenna are tested to detect the PD signals emitted from 1300 MHz to 1900 MHz range [13]. In [14], fractal antenna is designed to operate on various impedance bandwidth (narrowband, wideband, or multiband) by adjusting the antenna dimensions. In [15], the Vivaldi antenna is designed to operate from 510 MHz to 825 MHz and 950 MHz to 2 GHz.…”
Section: Introductionmentioning
confidence: 99%
“…In substation, noise is usually prevalent at lower frequency range (less than 200 MHz), which can be easily eliminated by the UHF based PD detection [9]. In [10] [6,[11][12][13], fractal antenna [14,15], Hilbert antenna [16,17], Archimedean antenna [18] and microstrip patch antenna [19][20][21]. However, most of these antennas are directional antenna.…”
Section: Introductionmentioning
confidence: 99%